Investigación de fenómenos psicosociales Una aproximación para el encuentro con el otro - Carmona-Toro, Paola Andrea (Universidad Católica Luis Amigó, 2021)
The book "Investigación de fenómenos psicosociales". An approach for the encounter with the other is an initiative of some researchers of the Psychology program of the Manizales Regional Center of the Catholic University Luis Amigó, due to the exponential growth of research in phenomena that shape the social reality of our context and the interest of problematizing research as an option of encounter with people and communities, rethinking traditional and extractivist notions in the construction of knowledge. With this initiative, it is evident that the research processes carried out throughout the years of existence of the Psychology program, have been interlocated, accompanied and fed back by academic agents from other institutions, which has significantly nurtured the discussions. In addition, the production presents a common denominator, and that is qualitative research, as a recurrent design in the different studies, becoming a device for the problematization of the text.